KECAMATAN DUDUKSAMPEYAN KABUPATEN GRESIK - Dandy Nugroho; Akhmad Andi Saputra; muhammad Fiqih Febrianto (Wahana Teknik, 2022)
The need for clean water in Tambak Rejo Village is very large. The population in 2022 is ± 2,100 people. This village does not yet have a clean water distribution network, the community generally uses seasonal water sources such as reservoirs and lakes which in the dry season will dry up. Therefore, researchers feel the need to plan a clean water network with the aim of meeting water needs in the village. This study includes population projections in 2027, water needs, design of pipe installation patterns, and calculation of the budget plan needed in planning the piping network in Tambak Rejo Village. The conclusions of this study are: 1. The results of the projected analysis of the population of Tambak Rejo Village in 2027 are as many as 2,278 people and for the water needs of the residents of Tambak Rejo Village in 2027 it is 374,773 liters/day or equal to 4.34 liters/second. 2. The pipe used is HDPE pipe because it is very suitable with the characteristics of the region, and is very strong. The diameter that can be used from the analysis results are two types of sizes, namely pipes with a size of 63 mm and 90 mm. 3. Planning for the installation of a water pipe network in Tambak Rejo village requires a fee of IDR. 554,380,000.00- (five hundred fifty-four million three hundred and eighty-nine thousand rupiah).